Treatment with Evasin-3 Reduces Atherosclerotic Vulnerability for Ischemic Stroke, but Not Brain Injury in Mice. Issue 4 (April 2013) - Copin, Jean-Christophe; da Silva, Rafaela F; Fraga-Silva, Rodrigo A; Capettini, Luciano; Quintao, Silvia; Lenglet, Sé bastien; Pelli, Graziano; Galan, Katia; Burger, Fabienne; Braunersreuther, Vincent; Schaller, Karl; Deruaz, Maud; et al.
Neutrophilic inflammation might have a pathophysiological role in both carotid plaque rupture and ischemic stroke injury. Here, we investigated the potential benefits of the CXC chemokine-binding protein Evasin-3, which potently inhibits chemokine bioactivity and related neutrophilic inflammation in two mouse models of carotid atherosclerosis and ischemic stroke, respectively. In the first model, the chronic treatment with Evasin-3 as compared with Vehicle (phosphate-buffered saline (PBS)) was investigated in apolipoprotein E-deficient mice implanted of a 'cast' carotid device. In the second model, acute Evasin-3 treatment (5 minutes after cerebral ischemia onset) was assessed in mice subjected to transient left middle cerebral artery occlusion. Although CXCL1 and CXCL2 were upregulated in both atherosclerotic plaques and infarcted brain, only CXCL1 was detectable in serum. In carotid atherosclerosis, treatment with Evasin-3 was associated with reduction in intraplaque neutrophil and matrix metalloproteinase-9 content and weak increase in collagen as compared with Vehicle. In ischemic stroke, treatment with Evasin-3 was associated with reduction in ischemic brain neutrophil infiltration and protective oxidants. No other effects in clinical and histological outcomes were observed. We concluded that Evasin-3 treatment was associated with reduction in neutrophilic inflammation in both mouse models. However, Evasin-3 administration after cerebral ischemia onset failed to improve poststroke outcomes.